SORPTION CORRECTION OF CHANGES IN IMMUNOLOGICAL REACTIVITYOF RATS UNDER EXPERIMENTAL CARCINOGENESIS AND APPLICATION OF CHEMOTHERAPEUTIC FACTORS - Soroka, Yu.V. (World of Medicine and Biology, 2013)
Expediency and nosotropic validity of application are experimentally confirmed carbon enterosorbent IV of generation of "Karbolaine" with the purpose of correction of violations of immunological reactivity for white rats in the conditions of experimental cancerogenesis on a background a chemotherapy. Normalization of functioning is marked humoral and cellular links of the immunity system, diminishing of maintenance of immune complexes in blood of experimental animals, and also the expressed decline of apoptic and necrotic changed CD - 3 лимфоцитов in tissues of liver and kidney.
Keywords: immunological reactivity; chemotherapy; sorbent